Glandular trichomes, histochemical localization of secretion, and essential oil composition in Plectranthus grandidentatus growing in Portugal†. (16th August 2013) - Mota, Luísa; Figueiredo, Ana Cristina; Pedro, Luis G.; Barroso, José G.; Ascensão, Lia; Figueiredo, Ana Cristina; Rubiolo, Patrizia
ABSTRACT Glandular trichomes and essential oils of Plectranthus grandidentatus grown in Portugal were studied for the first time. Trichome types and their distribution pattern were investigated by light and scanning electron microscopy. Three distinct types of glandular trichomes were described on the vegetative organs. Peltate trichomes, confined to the leaf abaxial surface, showed an orange–brownish characteristic colour and never developed a large subcuticular space. Digitiform and capitate trichomes were distributed on both leaf surfaces, the last being divided in two subtypes according to the dimension of the head, length of stalk and secretion process. In addition to these trichome types, flowers also exhibit uncommon conoidal glandular trichomes. Histochemical characterization of secretion revealed the presence of terpenoids and flavonoids as main constituents. Essential oils, isolated by hydrodistillation of aerial organs, harvested at the four calendar‐based seasons, were analysed by gas chromatography and gas chromatography–mass spectrometry. The oils with a dark–orange colour and agreeable odour were obtained in yields that ranged from 0.2 to 0.5% (v/d.w.). Sesquiterpenes constituted the dominant fraction (69–79%), β‐caryophyllene (9–13%) and δ‐cadinene (5–7%) being the most abundant hydrocarbons in all oils and β‐caryophyllene oxide (4–8%) and 14‐hydroxy‐9‐epi‐(E)‐caryophyllene (4–6%) the major oxygen‐containing compounds. The monoterpene fraction did not exceed 13%, oxygen‐containing diterpenes attained lower percentages (1–9%), and phenylpropanoids were only present in trace amounts. The essential oils isolated from plants collected during the vegetative phase (winter and spring) showed a similar chemical profile, while that isolated from plants harvested in summer, resembled the one obtained from plants in the flowering phase collected in autumn. Copyright © 2013 John Wiley & Sons, Ltd.